Reclaiming the subject: A buddhist perspective on consciousness studies - Masís Iverson, Katherine (2015)
This paper highlights the importance of the subject in consciousness studies.  It begins with the “hard problem” of the mind-body nexus according to David Chalmers, Thomas Nagel and Colin McGinn.  Materialism and dualism are portrayed in contrast with Buddhist ontology, followed by a brief description of Francisco Varela’s neurophenomenology.  Finally, Buddhist meditation is presented as a valid introspective method that vindicates the role of the subject in consciousness studies.